Preface to selected papers from 22nd Workshop on Programming and Languages (PROLE 2023) - Panizo, Laura (Journal of logical and algebraic methods in programming, 2025)
This special issue collects extended versions of selected papers presented at the 22nd Workshop on Programming and Languages (PROLE 2023), held in Ciudad Real from September 12 to 14, 2023.